Racial differences in patient perception of interactions with providers are associated with health outcomes in type II diabetes. Issue 8 (August 2021) - Reid, Hadley W.; Lin, Olivia M.; Fabbro, Rebecca L.; Johnson, Kimberly S.; Svetkey, Laura P.; Olsen, Maren K.; Matsouaka, Roland A.; Chung, Sangyun Tyler; Batch, Bryan C.
Highlights: Explanation of results and medications is associated with better glycemic control. Hurried communication is associated with worse glycemic control. The above associations are present for non-Hispanic Black patients, not Whites. Disrespectful office staff are associated with poor diabetes medication adherence. Discrimination is associated with more missed appointments. Abstract: Objectives: Examine the association of patient perceptions of care with hemoglobin A1c (HbA1c), medication adherence, and missed appointments in non-Hispanic Black (NHB) and White (NHW) patients with type 2 diabetes (T2DM). Methods: We used linear and logistic regression models to analyze the association of the Interpersonal Processes of Care survey (IPC) with HbA1c, medication adherence, and missed appointments. We then examined how these associations differed by race. Results: There was no overall association between IPC subdomains and HbA1c in our sample (N = 221). NHB patients perceiving their provider always explained results and medications had a HbA1c on average 0.59 (-1.13, -0.04; p = 0.04) points lower than those perceiving their provider sometimes explained results and medications. No effect was observed in NHWs. Never perceiving disrespect from office staff was associated with an average 0.67 (-1.1, -0.24; p = 0.002) point improvement in medication adherence for all patients. Never perceiving discrimination from providers was associated with a 0.44 (-0.63, -0.25; p < 0.0001) decrease in the probability of missing an appointment for NHB patients. Conclusions: These results demonstrate that particular aspects of communication in the patient-provider interaction may contribute to racial disparities in T2DM. Practice Implications: Communication training for both providers and staff may reduce disparities in T2DM.